2015
DOI: 10.3892/or.2015.4350
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate induces mitochondria-dependent apoptosis and inhibits invasion of human pigmented villonodular synovitis fibroblast-like synovial cells

Abstract: Pigmented villonodular synovitis (PVNS) is a rare sarcoma-like disorder characterized by synovial lesions proliferation and invasion to articular cartilage for which no effective treatments are available. Imatinib mesylate (IM) is known to exert antitumor activity in some tumors, but its effects on PVNS fibroblast-like synoviocytes (PVNS-FLS) and the specific mechanism involved remain to be established. In the present study, the in vitro effects of IM on cell proliferation and survival rates were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…According to the CCK-8 assay result and previous studies, 100 μ M of OLA was used for the in vitro experiment [ 14 ]. Recently, some studies have found that mitochondrial dysfunction was involved in synovitis [ 16 ]. SIRT3 is located in the mitochondria and regulates mitochondrial function.…”
Section: Resultsmentioning
confidence: 99%
“…According to the CCK-8 assay result and previous studies, 100 μ M of OLA was used for the in vitro experiment [ 14 ]. Recently, some studies have found that mitochondrial dysfunction was involved in synovitis [ 16 ]. SIRT3 is located in the mitochondria and regulates mitochondrial function.…”
Section: Resultsmentioning
confidence: 99%
“…TGCT progresses slowly [21]. However, it causes local destruction with invasion of the adjacent joint cartilage [22], and more severe symptoms such as joint pain, limited range of motion, swelling, erythema, and hemorrhagic effusion [23]. Excision by arthroscopic or open synovectomy is recommended, but complete removal is sometimes difficult to achieve due to the wide spread of the growth, resulting in high local recurrence [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Pigmented villonodular synovitis, also known as tenosynovial giant-cell tumor, is a rare synovial proliferative disease with an incidence of 1.8 cases per 1 million people (Chen et al, 2015). Due to its rare incidence, the disease remains a diagnostic challenge.…”
Section: Historymentioning
confidence: 99%